Overeducation in the Australian graduate labour market - Li, Ian W. (Curtin University, 2013)
The uptake of university education in Australia has increased in recent years. At the same time, studies in Australia and elsewhere have indicated that substantial imbalances exist between the labour demand for, and supply of, highly qualified individuals, and that this may result in unfavourable labour market outcomes. This thesis explores these types of issues in the Australian graduate labour market, using data on Australian university graduates from 1999 to 2009, with a focus on education-job mismatch and its consequences.In the empirical analyses, the incidence, determinants and labour market outcomes of education-job mismatch are explored. The research also examines the earnings impacts of education-job mismatch on segments of the Australian graduate labour market. Specifically, the gender, institutional and length of job tenure differences in education-job mismatch and earnings effects are explored. The research in these areas will be of help in providing information on issues such as the gender wage gap, and the deregulation of university fees. This thesis makes valuable contributions to the literature in at least two aspects. First, the increase in university education attainment in Australia has been fuelled by policy changes in the higher education sector in recent years. The findings of the thesis will, therefore, be timely in adding to the debate on these changes, at least from a labour market perspective. Second, the methodology used in the examination of education-job mismatch and graduate earnings has not been used in any other studies, as far as the author is aware.A substantial proportion of Australian graduates are found to be mismatched, in that they possess qualifications higher than that required for their jobs. This has been shown to lead to adverse earnings consequences, particularly for those with large extents of education-job mismatch. Policy implications arising from the findings of the analyses are provided, and directions for future research are given in the concluding chapter.